Applicability of Pulse Pressure Variation during Unstable Hemodynamic Events in the Intensive Care Unit: A Five-Day Prospective Multicenter Study. (31st March 2016) - Delannoy, Bertrand; Wallet, Florent; Maucort-Boulch, Delphine; Page, Mathieu; Kaaki, Mahmoud; Schoeffler, Mathieu; Alexander, Brenton; Desebbe, Olivier
Abstract : Pulse pressure variation can predict fluid responsiveness in strict applicability conditions. The purpose of this study was to describe the clinical applicability of pulse pressure variation during episodes of patient hemodynamic instability in the intensive care unit. We conducted a five-day, seven-center prospective study that included patients presenting with an unstable hemodynamic event. The six predefined inclusion criteria for pulse pressure variation applicability were as follows: mechanical ventilation, tidal volume >7 mL/kg, sinus rhythm, no spontaneous breath, heart rate/respiratory rate ratio >3.6, absence of right ventricular dysfunction, or severe valvulopathy. Seventy-three patients presented at least one unstable hemodynamic event, with a total of 163 unstable hemodynamic events. The six predefined criteria for the applicability of pulse pressure variation were completely present in only 7% of these. This data indicates that PPV should only be used alongside a strong understanding of the relevant physiology and applicability criteria. Although these exclusion criteria appear to be profound, they likely represent an absolute contraindication of use for only a minority of critical care patients.